Modeling the challenges affecting the internationalization of the Persian Gulf Pro League - Sajad Soroush; Geoff Dickson; Nasrollah Sajjadi; Ebrahim Alidoust Ghahfarokhi (Sport Sciences and Health Research)
Background: Internationalization of sports leagues can have several benefits, including increased exposure to a global audience; improved competitiveness; and enhanced financial opportunities and cultural exchange. Overall, the internationalization of a sports league can help it grow, become more competitive, and reach a wider audience, leading to benefits for both the league and its fans. Aim: The main objective of this research was to develop a model of challenges affecting the internationalization of the Persian Gulf Pro League (PGPL). Materials and Methods: We conducted twenty in-depth interviews with expertise involved in the functioning of the PGPL who were recruited using a convenience sampling method. The data was analyzed using grounded theory method, including open, axial, and selective coding. During the analysis, we identified 85 codes that generated 49 general concepts. Subsequently, through further reviewing the concepts and their combination with each other, we identified twenty tow final categories that affect the internationalization of PGPL. These categories were classified into five main dimensions: political-economic; managerial; legal; technical-marketing and socio-cultural. Results: According to the research findings, it is necessary for the Iranian football managers and practitioners to first address the challenges affecting the internationalization of the PGPL and then provide the required conditions and platforms with attitude-behavioral alignment to move toward internationalization. Conclusion: The study suggests that Iranian football managers and practitioners need to address challenges hindering the internationalization of the PGPL and provide the necessary conditions and platforms to facilitate the process. By doing so, the PGPL can expand its presence and competitiveness in the global football industry, leading to growth and success.